FEATURES OF CLASSROOM ENVIRONMENT IN FIRST YEAR MAINSTREAM STUDENTS’ ENGLISH SPEAKING CLASSES – A MULTIPLE CASE STUDY - Chu, Thị Ngọc (2020)
This research focuses on finding out the classroom environment in two English speaking classes with different levels of motivation in the Faculty of English Language Teacher Education, University of Languages and International Studies, Vietnam National University, Hanoi. Eleven classes in this faculty took part in the first round by answering questionnaires to sort out which class was the most highly motivated and which one was the least motivated. After that, these two classes continued with the second step to investigate their classroom environment features. The question framework was based on the instrument Classroom Environment Scales (CES) of Moos and Trickett (1973) with nine factors. They are teacher, rule clarity, order and organization, innovation, student involvement, competition, affiliation, and task orientation. By using a forty-two item questionnaire, the researcher found out the features which were quite relevant to what was written in the literature. Teacher was very friendly, approachable, and humorous.